Comment On Nestlé USA, Inc. v. Doe: Ivory Coast Cocoa Farming Child Slaves, the Alien Tort Statute, And the “Craven Watchdog” - Adam Gray (Washington University Global Studies Law Review, 2025)
On 17 June, 2021, the Supreme Court published its decision in the case of Nestlé USA, Inc. v. Doe. The case was on appeal from the Court of Appeals for the Ninth Circuit. It was originally brought in the United States. District Court for the Central District of California. Six individuals from Mali (“Plaintiffs” or “Respondents”) claimed that they were trafficked into the Ivory Coast and held as child slaves, forced to work on cocoa farms that sold cocoa to Nestlé USA, Inc. (“Nestlé”). The Plaintiffs argued that Nestlé, which provided financial and technical support to the cocoa farms, despite not owning them, should be held liable under the Alien Tort Statute for aiding and abetting child slavery in violation of customary international law.
Keywords: Human Trafficking; Supreme Court of the United States; Mali; Cocoa Farms; Ivory Coast; Child Slaves; Alien Tort Statute